Teacher Perceptions of Multicultural Education and Diversity Values in the School Environment - Hariyadi, Bachtiar; Rodiyah, Siti Kholidatur (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
A comprehensive education system is essential to promote peace in a diverse, multicultural society. Teachers have a critical role in organizing the classroom environment, and it is vital to understand their perceptions of Multiculturalism and the extent to which educational programs adopt multicultural principles. This study investigated teachers' perceptions of multicultural education and diversity and evaluated their awareness of these issues. A qualitative research design with case studies was used, and six teachers from an elementary school in Surabaya were deliberately selected for this study. The data were collected through interviews, observation, and document analysis, and the results were analyzed using content analysis techniques. This study found that teachers have adequate knowledge about multicultural education and a positive attitude toward it. However, their understanding and prejudices related to specific concepts still need more. In addition, the inclusiveness of Multiculturalism in annual plans and teaching programs still needs to be improved. Learning transformation is required that encourages active student collaboration, such as the project-based learning (PjBL) model.